Outcome of ewing sarcoma in children, twenty years experience from a single center in Turkey - EKER, NURŞAH; TOKUÇ, AYŞE GÜLNUR; TRUE, ÖMER (My University, 2017)
Background/Objectives: Ewing sarcoma (ES) is the second common primary bone malignancy in pediatric patients. Usually, these tumors occur in bone but sometimes they can olsa orginate in soft tissue. These tumors are agressive and treatment involves multidurgs chemotherapy, radiotherapy and surgery. The aim of this study was to determine outcomes of Ewing sarcoma in pediatric patients who was treated in our instution. Design/Methods: This is a retrospective study of 75 pediatric patients with Ewing Sarcoma treated in between 1996 to 2016. Results: During a 20-year period, 75 patients were identified with Ewing Sarcoma in hospital database and their records were analyzed retrospectively. Of the 75 patients, 45 (60%) were males, 30 (40%) were females. The mean age was 10 years (ranging from 1year to 17 years). All of the patients had received the same chemotherapy protocol at presentation. This protocol involved ifosfamide, etoposide, vincristine, doxorubicine, cyclophosphamide and actinomycin. After 3 cycles of chemotherapy, surgery had been performed for most of the patients. Radiotherapy had been performed for the patients who had more than 10% viable cells after pathological examinations. For these patients, chemotherapy had been changed and continued during and after radiotherapy. The second chemotherapy protocol invoved vincristine, cyclophosphamide and topotecan. At the presentation, 22 (29 %) patients had metastatic disease. During the follow up 16 (23 %) patients had relapsed. The 5-year event free survival and overall survival were 46 % and 58,5 %. Metastatic disease at presentation was the significant factor on overall survival. Conclusions: The management of a child or adolescent with Ewing sarcoma is best carried out in a specialized center under the care of a multidisciplinary team, in order to obtain the best outcome for the patient. Early diagnosis is very important because metastatic disease at presentation reduces the overall survival.